Micro-Doppler frequency comb generation by rotating wire scatterers. (March 2017) - Kozlov, V.; Filonov, D.; Yankelevich, Y.; Ginzburg, P.
Abstract: Electromagnetic scattering in accelerating reference frames inspires a variety of phenomena, requiring employment of general relativity for their description. While the 'quasi-stationary field' analysis could be applied to slowly-accelerating bodies as a first-order approximation, the scattering problem remains fundamentally nonlinear in boundary conditions, giving rise to multiple frequency generation (micro-Doppler shifts). Here a frequency comb, generated by an axially rotating subwavelength (cm-range) wires is analyzed theoretically and observed experimentally by illuminating the system with a 2 GHz carrier wave. Highly accurate 'lock in' detection scheme enables factorization of the carrier and observation of multiple peaks in a comb. The Hallen integral equation is employed for deriving the currents induced on the scatterer and a set of coordinate transformations, connecting laboratory and rotating frames, is applied in order to make analytical predictions of the spectral positions and amplitudes of the frequency comb peaks. Numeric simulations of the theoretic framework reveal the dependence of the micro-Doppler peaks on the wire's length and its axis of rotation. Unique spectral signature of micro-Doppler shifts could enable resolving internal structures of scatterers and mapping their accelerations in space, which is valuable for a variety of applications spanning from targets identification to stellar radiometry. Highlights: Electromagnetic theory of scattering from rotating bodies with nontrivial geometries. Lock in detection scheme for slow accelerations. Micro-Doppler frequency comb analysis and detection.